Doxorubicin - Cyclophosphamide Protocol in Dogs with Splenic Haemangiosarcoma and Haemoabdomen: A Retrospective Case Series - del Castillo, Noemí; Fuertes-Recuero, Manuel; De Angelis, Elisabetta; de la Riva, Claudia; García, Cristina; Rayón, Noemí; Márquez, Sandra; Ortiz-Díez, Gustavo (MDPI, 2025)
This retrospective case series describes 21 dogs with stage II splenic haemangiosar coma (HSA) and spontaneous haemoabdomen treated with splenectomy followed by a doxorubicin¿cyclophosphamide protocol. Median overall survival was 92 days, with longer survival observed in dogs completing three or more chemotherapy cycles. The regimen was well tolerated, with low haematological and gastrointestinal toxicity. Mainte nance metronomic chemotherapy was administered in a small subset, and it was associated with prolonged survival. While the sample size is modest, the homogeneous and clinically specific cohort provides hypothesis-generating observations on feasibility, tolerability, and time-aware associations that warrant cautious interpretation and prospective confirmation. No clinical or laboratory variable at diagnosis was independently associated with outcome. While limited by retrospective design and small sample size, this study provides focused data on a specific clinical presentation and supports the feasibility of structured adjuvant treatment in dogs with splenic HSA and haemoabdomen.